Condensations based on 5‐(indol‐3‐yl)‐pyrrolidin‐2‐thiones. Issue 4 (20th November 2018) - Sadovoy, Andrey V.; Kattsyna, Veronica V.; Protopopova, Polina S.; Nelyubina, Yulia V.; Pavlov, Alexander A.; Kochetkov, Konstantin A.; Sviridova, Lyudmila A.
Abstract: New activated indolylpyrrolidones—their methylthiopyrrolinium salts—in the reactions with several CH‐acids were studied. 2‐Nitromethylene‐ and 2‐dicyanomethyleneindolylpyrrolidines were obtained from 5‐indolyl‐2‐methylthiopyrrolinium salts with good yields. The reduction in these nitro compounds yields the respective aminomethylpyrolidines. The rigid structure of the starting compounds has significant stereoelectronic requirements of nucleophilic agents.